Multilingual educational practices at pre-primary level in Slovenia, Austria, Italy and Croatia - Žefran, Mojca (Revija za elementarno izobraževanje, 2024)
The paper presents findings from a scoping review of scientific articles, projects, networks, and legal documents concerning multilingual practices at the pre-primary level in Slovenia, Croatia, Austria, and Italy aimed at exploring the extent and nature of multilingual educational practices, as well as research findings related to multilingual education at the pre-primary level in these countries. The primary objective was to assess the current situation, challenges, and future prospects of multilingual practices in preschool institutions. The results offer valuable insights into multilingual practices in these countries, highlighting the need for enhancing teachers' competence to effectively work in linguistically diverse environments.
Keywords: jezikovna in kulturna raznolikost; linguistic and cultural diversity; multiculturalism; multilingual preschool education; multilingualism; večjezična predšolska vzgoja; večjezičnost; večkulturnost